Authenticating Raw from Reconstituted Milk Using Fourier Transform Infrared Spectroscopy and Chemometrics - Lijuan Du; Weiying Lu; Boyan Gao; Jing Wang; Liangli (Lucy) Yu (Journal of Food Quality)
Fourier transform infrared (FTIR) spectroscopy combined with chemometrics was used to authenticate raw milk from their reconstituted counterparts. First, the explanatory principal component analysis (PCA) was employed to visualize the relationship between raw and reconstituted milk samples. However, the degree of separation between two sample classes was not significant according to direct observation of the scores plot, indicating FTIR spectra may contain complicated chemical information. Second, partial least-squares-discriminant analysis (PLS-DA) that incorporate additional class membership information as modelling input was further calculated. The PLS-DA scores yielded clear separation between two classes of samples. Additionally, possible components from the model loading were studied, and the PLS-DA model was validated internally under the model population analysis framework, as well as externally using an independent test set. This study gave insights into the authentication of milk using FTIR spectroscopy with chemometrics techniques.